2020
DOI: 10.1186/s12888-020-02742-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors associated with postoperative delirium following primary elective total hip arthroplasty: a retrospective nationwide inpatient sample database study

Abstract: Background: Postoperative delirium is a common complication following major surgeries, leading to a variety of adverse effects. However, there is a paucity of literatures studying the incidence and risk factors associated with delirium after primary elective total hip arthroplasty (THA) using a large-scale national database. Methods: A retrospective database analysis was performed based on Nationwide Inpatient Sample (NIS) from 2009 to 2014. Patients who underwent primary elective THA were included. Patient de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…Consistent with the previous studies [ 27 , 28 ], the present study demonstrated that hypertension was strongly associated with both incidence and severity of PD following TJA, and this condition was especially in patients with moderate to severe hypertension. According to the previous studies [ 29 , 30 ], hypertension is significantly associated with increased endothelial dysfunction and atherosclerosis, thus leading to an increased risk of cerebral embolization.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the previous studies [ 27 , 28 ], the present study demonstrated that hypertension was strongly associated with both incidence and severity of PD following TJA, and this condition was especially in patients with moderate to severe hypertension. According to the previous studies [ 29 , 30 ], hypertension is significantly associated with increased endothelial dysfunction and atherosclerosis, thus leading to an increased risk of cerebral embolization.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the previous studies [27,28], the present study demonstrated that hypertension was especially associated with PD following TJA. According to the previous studies [29,30], hypertension is signi cantly associated with increased endothelial dysfunction and atherosclerosis, thus leading to an increased risk of cerebral embolization.…”
Section: Discussionsupporting
confidence: 93%
“…In this prospective study, every delirium case was confirmed by the skillful geriatric psychiatrist. Moreover, it was also proved in the multivariable logistic regression model, in which anxiety, age, alcohol abuse, education level and stroke history were detected as predictors that were also reported in some researches [26,41,42]. As anxiety was a quite common symptom before surgery.…”
Section: Discussionmentioning
confidence: 56%